2022
DOI: 10.5858/arpa.2021-0510-oa
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Sequencing as a New Comprehensive Technology for Identifying Rare α- and β-Globin Gene Variants in Thalassemia Alleles in the Chinese Population

Abstract: Context.— Identification of rare thalassemia variants requires a combination of multiple diagnostic technologies. Objective.— To investigate a new approach of comprehensive analysis of thalassemia alleles based on third-generation sequencing (TGS) for identification of α- and β-globin gene variants. Design.— Enrolled in this study were 70 suspected carriers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The third-generation sequencing based on PacBio Sequel II platform for globin genes variants detection was conducted as the description of our previous study 16 . Genomics DNA were extracted and then sent to Berry Genomics laboratory for third-generation sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The third-generation sequencing based on PacBio Sequel II platform for globin genes variants detection was conducted as the description of our previous study 16 . Genomics DNA were extracted and then sent to Berry Genomics laboratory for third-generation sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…After purification and end repair, double barcode adaptors were ligated to the 5’ and 3’ ends and Sequel Binding and Internal Ctrl Kit 3.0 (PacBio) was used to prepare SMRT bell libraries. Finally, third-generation sequencing was performed on the PacBio Sequel II System after primed DNA-polymerase complexes were loaded onto the SMRT cells 16 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TGS can detect both known and unknown variants and determine whether two or more variants are in cis- or trans-configurations ( Ardui et al, 2018 ; Liu et al, 2022 ). The clinical utility of a third-generation sequencing-based approach termed comprehensive analysis of thalassemia alleles (CATSA) in carrier screening of thalassemia was vigorously validated in blind clinical studies with a large cohort of samples, and CATSA demonstrated great advantages in terms of detecting range and accuracy compared to routine PCR and multiple ligation-dependent probe amplification ( Liang et al, 2021 ; Luo et al, 2022 ; Zhuang et al, 2022 ). In this study, the previous CATSA method was modified to cover more thalassemia variants.…”
Section: Introductionmentioning
confidence: 99%